Lie detection in the brain - Moral, social, legal and religious challenges - Poulou, Chrysa G (Bioethica, 2021)
Lie detection and recognition has been an ardent human desire since ancient times. Over the centuries, various methods have been devised to detect fraud. Some methods are low-tech, like the recognition of specialized facial expressions, while others use devices, such as the polygraph or "lie detector" designed in the early 20th century, which measure changes in human body like sweating, heart rate and blood pressure, in order to detect the lie. These methods have various applications in areas such as justice, the military and the secret services. Recent attempts to detect falsehood have focused on measuring brain activity. This approach, unlike previous emotional arousal methods, detects physiological changes associated with cognitive processes during deception and therefore, according to the proponents of the technique, could detect the process of deception itself. The most well-known method of detecting a "neurophysiological difference between deception and truth" in the brain is functional Magnetic Resonance Imaging (fMRI), an MRI brain scan which reveals that deception is located in the prefrontal cortex, just behind the forehead. However, how accurate and reliable are these “brain mapping” approaches to detect lies? What are the moral, legal, religious and social issues arising from the “invasion” of so-called neuroscience into personal data, individual freedom, and the right of non-self-incrimination and the "free will" of human beings? Critical questions, addressed in this paper, in an attempt to approach lie detection in the brain and the challenges - concerns that may determine the way we perceive human society in the future.